Development of Al-Qur'an Interpretation Research in the Digital Era: Bibliometric Approach with R for Statistical Computing - Fadhilah, Umi; Nugroho, Kharis; Azizah, Alfiyatul (Universitas Muhammadiyah Surakarta, 2023)
This research aims to understand the mapping of the development and research directions of various articles related to Quranic interpretation in publications indexed in the Scopus database. This includes methods, products, interpreters, and their implementations. The method employed is bibliometric analysis, which explores all publications indexed in the Scopus database from 1994 to 2023. Subsequently, the data is analyzed using Excel and R/R-Studio. Further analysis is carried out using VOSviewer to visually analyze keyword occurrences and document citations simultaneously. Based on the various analyses conducted, the authors found 189 publications that met the defined criteria, indicating an annual growth rate of 3.86%, with the highest number of publications in the year 2022. Malaysia contributed the most publications, with affiliations from the National University of Malaysia. Ibrahim, M. and Kadir, M.N.A. emerged as the most productive authors in the field of Quranic interpretation. The journals that published the most on the theme of Quranic interpretation were Cumhuriyet Ilahiyat Dergisi, Al Bayan, and Journal of Qur'anic Studies. It is important to note that this bibliometric analysis was limited to Scopus data, and other national and international databases were not considered in this study. This research provides a brief overview of literature accessible to researchers working in the field of Quranic interpretation and offers recommendations for future research.